Genomic monitoring of the SARS-CoV-2 B1.1.7 (WHO VOC Alpha) in the Sao Paulo state, Brazil - Slavov, Svetoslav Nanev; Bezerra, Rafael dos Santos; Rodrigues, Evandra Strazza; Santos, Elaine Vieira; Borges, Joseane Serrano; de la Roque, Débora Glenda Lima; Patané, José Salvatore Leister; Lima, Alex Ranieri Jerônimo; Ribeiro, Gabriela; Viala, Vincent Louis; de Lima, Loyze Paola Oliveira; Martins, Antonio Jorge; et al. (Elsevier, 2022)
The SARS-CoV-2 alpha VOC (also known as lineage B.1.1.7) initially described in the autumn, 2020 in UK, rapidly became the dominant lineage across much of Europe. Despite multiple studies reporting molecular evidence suggestive of its circulation in Brazil, much is still unknown about its genomic diversity in the state of São Paulo, the main Brazilian economic and transportation hub. To get more insight regarding its transmission dynamics into the State we performed phylogenetic analysis on all alpha VOC strains obtained between February and August 2021 from the Sao Paulo state Network for Pandemic Alert of Emerging SARS-CoV-2 variants. The performed phylogenetic analysis showed that most of the alpha VOC genomes were interspersed with viral strains sampled from different Brazilian states and other countries suggesting that multiple independent Alpha VOC introductions from Brazil and overseas have occurred in the São Paulo State over time. Nevertheless, large monophyletic clusters were also observed especially from the Central-West part of the São Paulo State (the city of Bauru) and the metropolitan region of the São Paulo city. Our results highlight the Alpha VOC molecular epidemiology in the São Paulo state and reinforce the need for continued genomic surveillance strategies for the real-time monitoring of potential emerging SARS-CoV-2 variants during the ever-growing vaccination process.
Keywords: Alpha VOC; B.1.1.7; Brazil; Genomic surveillance; SARS-CoV-2; São Paulo